Citrus essential oils : flavor and fragrance - Sawamura, Masayoshi (John Wiley & Sons, 2010)
This book provides an overview of citrus essential oils, covering basics, methodology, and applications involved in recent topics of citrus essential oils research. It describes the concepts, analytical methods, and properties of these oils